The jasmonate biosynthesis Gene OsOPR7 can mitigate salinity induced mitochondrial oxidative stress. (March 2022) - Asfaw, Kinfemichael Geressu; Liu, Qiong; Eghbalian, Rose; Purper, Sabine; Akaberi, Sahar; Dhakarey, Rohit; Münch, Stephan W.; Wehl, Ilona; Bräse, Stefan; Eiche, Elisabeth; Hause, Bettina; Bogeski, Ivan; et al.
Highlights: OsOPR7-GFP protein is correctly localized in peroxisomes. Mitochondria, peroxisomes, and plastid communicate each other. OsOPR7 overexpressor cells shift jasmonate metabolism towards OPDA. Plant PeptoQ and OsOPR7 do not act additively, although they act in different locations. Abstract: Salinity poses a serious threat to global agriculture and human food security. A better understanding of plant adaptation to salt stress is, therefore, mandatory. In the non-photosynthetic cells of the root, salinity perturbs oxidative balance in mitochondria, leading to cell death. In parallel, plastids accumulate the jasmonate precursor cis (+)12-Oxo-Phyto-Dienoic Acid (OPDA) that is then translocated to peroxisomes and has been identified as promoting factor for salt-induced cell death as well. In the current study, we probed for a potential interaction between these three organelles that are primarily dealing with oxidative metabolism. We made use of two tools: (i) Rice OPDA Reductase 7 (OsOPR7), an enzyme localised in peroxisomes converting OPDA into the precursors of the stress hormone JA-Ile. (ii) A Trojan Peptoid, Plant PeptoQ, which can specifically target to mitochondria and scavenge excessive superoxide accumulating in response to salt stress. We show that overexpression of OsOPR7 as GFP fusion in tobacco ( Nicotiana tabacum L. cv. Bright Yellow 2, BY-2) cells, as well as a pretreatment with Plant PeptoQ can mitigate salt stress with respect to numerous aspects including proliferation, expansion, ionic balance, redox homeostasis, and mortality. This mitigation correlates with a more robust oxidative balance, evident from a higher activity of superoxide dismutase (SOD), lower levels of superoxide and lipid peroxidation damage, and a conspicuous and specific upregulation of mitochondrial SOD transcripts. Although both, Plant PeptoQ and ectopic OsOPR7, were acting in parallel and mostly additive, there are two specific differences: (i) OsOPR7 is strictly localised to the peroxisomes, while Plant PeptoQ found in mitochondria. (ii) Plant PeptoQ activates transcripts of NAC, a factor involved in retrograde signalling from mitochondria to the nucleus, while these transcripts are suppressed significantly in the cells overexpressing OsOPR7 . The fact that overexpression of a peroxisomal enzyme shifting the jasmonate pathway from the cell-death signal OPDA towards JA-Ile, a hormone linked with salt adaptation, is accompanied by more robust redox homeostasis in a different organelle, the mitochondrion, indicates that cross-talk between peroxisome and mitochondrion is a crucial factor for efficient adaptation to salt stress.